Morphological changes in four azolla genotypes concurrently grown with irrigated lowland rice - Parot-Alcantara, Virginia; Lales, Joveno S. (1992)
A field experiment was conducted to evaluate the morphological response of four azolla genotypes to declining solar irradiance beneath a rice canopy at different stages of development. Sporophyte size, root length and root-shoot ratio were higher under full sunlight than under shaded conditions. The adverse effect of low irradiance was most distinct when light interception was about maximum. Genotypic differences with respect to morphological response to declining irradiance were significant.
Keywords: Azolla; Plant morphology